Six minute walk distance and reference values in healthy Italian children: A cross-sectional study - Vandoni, Matteo; Correale, Luca; Puci, Mariangela Valentina; Galvani, Christel; Codella, Roberto; Togni, Fabio; La Torre, Antonio; Casolo, Francesco; Passi, Alberto; Orizio, Claudio; Montomoli, Cristina (PloS one, 2018)
The 6-minute walking test (6MWT) is a simple assessment tool to evaluate exercise capacity. The result of the test is the distance that a subject can walk at a constant and normal pace within 6 minutes (6MWD) and reflects the aerobic/fitness performance related to walking function. Use of 6MWT has been relevant to assess exercise tolerance either in healthy children or in patients with, heart, lung and metabolic diseases. Our aim was to find 6MWT reference values in healthy Italian children. The 6MWT was performed in 5614 children aged 6-11 years recruited from primary Italian schools. Age related reference percentiles of the covered distance were gender-modeled. A linear and quadratic regression model was used to predict 6MWT performance. Males walked longer distances than females, respectively 598.8±83.9 m vs 592.1±77.6 m (p = 0.0016). According to the regression analysis, 6MWD was positively related to age, gender and height, while it was negatively related to body weight [(6MWD = -160.16 + 93.35× age (years) -4.05× age2 (years) +7.34× gender (m) +2.12× weight (kg) -2.50× height (cm)]. Reference values were established for the 6MWT in healthy children. The age related 6MWD percentiles provided a useful tool in the assessment of capacity in 6-11 year children, in fact they may be helpful to evaluate the effect of a given treatment or rehabilitation program and represent a feasible measure as to prevention within the primary school context. It was found a substantial difference from other countries for 6mwd values. In our study, factors such as age, weight and height were relevant for the prediction of 6MWD, similarly to other studies. Therefore, these variables should be taken into account in context of exercise performance.